Committee systems in Portugal and Spain - Fernandes, Jorge (2019)
Legislative committees are the workhorses of efficient parliaments. LaPolambora highlights that "if the national legislature is to be a significant political actor, then it must have specialized committees of limited membership and considerable scope" (1974:123). Together with political parties, committees offer the organizational arena to aggregate preferences, curb transaction costs and facililate information acquisition and dissemination (Strøm 1998). According to Sartori, committees are optimal decision-making bodies because they "shun majority rule, seek unanimous agreements via internal deferred payments, and adjust to the outer world, or incorporate its demands, via side payments" (1987 236).